Penerapan Kurikulum Merdeka Pada Mata Pelajaran Pendidikan Pancasila Dalam Meningkatkan Nilai-Nilai Nasionalisme Pada Siswa - Al Amin; Suttrisno Suttrisno (Jurnal Pendidikan dan Kewarganegara Indonesia, 2024)
This research aims to instill and strengthen the spirit of democracy and nationalism in every student. When they have the spirit of democracy and nationalism, their love for the nation and enthusiasm for fighting for this nation will be strong and great. One effort to instill a spirit of democracy and nationalism in the next generation is by learning Pancasila and citizenship education. The type of method used in this article is a literature review. The writing of this literature review adopts national articles published on various journal provider platforms on a national scale which discuss the importance of increasing democratic values ​​and nationalism in students through learning Pancasila and citizenship education. The results of the research show that increasing democratic values ​​and nationalism in students through learning Pancasila and citizenship education shows a positive direction. This means that students who have received Pancasila and citizenship education material have experienced a good improvement in their democratic attitudes and nationalist feelings. This learning is implemented in Indonesia with the aim of forming students into individuals who have strong character and are based on the values ​​of Pancasila, who have faith and devotion to God Almighty, have global diversity, mutual cooperation, independence, critical reasoning and creativity. Apart from that, through Pancasila and citizenship education we are present to provide in-depth understanding from teachers about the essence of Pancasila and the urgency of citizenship education.